Kinematics of multiaxes prothetic knee for Alpine skiing - Demsar, I.; Duhovnik, J.; Lesnik, B.; Supej, M. (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
The purpose of this study is to simulate a regular two-track skiing with an above-knee amputation in a laboratory and to analyze rotations in knee joints in a prosthetic (right) and intact (left) leg.